Fabrication of Non‐enzymatic Electrochemical Glucose Sensor Based on Pd−Mn Alloy Nanoparticles Supported on Reduced Graphene Oxide. Issue 6 (7th February 2020) - Waqas, Muhammad; Lan, Jianjun; Zhang, Xiaoxia; Fan, Youjun; Zhang, Panyu; Liu, Chengzhou; Jiang, Zhe; Wang, Xiaoqu; Zeng, Jianqiang; Chen, Wei
Abstract: Mixed metals alloy nanoparticles supported on carbon nanomaterial are the most attractive candidates for the fabrication of non‐enzymatic electrochemical sensor with enhanced electrochemical performance. In this study, palladium‐manganese alloy nanoparticles supported on reduced graphene oxide (Pd−Mn/rGO) are prepared by a simple reduction protocol. Further, a novel enzyme‐free glucose sensing platform is established based on Pd−Mn/rGO. The successful fabrication of Pd−Mn alloy nanoparticles and their attachment at rGO are thoroughly characterized by various microscopic and spectroscopic techniques such as XRD, Raman, TEM and XPS. The electrochemical activity and sensing features of designed material towards glucose detection are explored by amperometric measurments in 0.1 M NaOH at the working voltage of −0.1 V. Thanks to the newly designed Pd−Mn/rGO nanohybrid for their superior electrorochemical activity towards glucose comprising the admirable sensing features in terms of targeted selectivity, senstivity, two linear parts and good stability. The enhanced electrochemical efficacy of Pd−Mn/rGO electrocatalyst may be credited to the abundant elecrocatalytic active sites formed during the Pd−Mn alloying and the electron transport ability of rGO that augment the electron shuttling phenomenon between the electrode material and targeted analyte. Abstract :